Critical Insights Into the Ecological and Invasive Attributes of Leucaena leucocephala, a Tropical Agroforestry Species - Sharma, Padma; Kaur, Amarpreet; Batish, Daizy R.; Kaur, Shalinder; Chauhan, Bhagirath S. (Frontiers in Agronomy, 2022)
Leucaena leucocephala (Lam.) de Wit (commonly known as leucaena) is a leguminous species of the family Fabaceae and a native of Mexico and Central America. It is often addressed as a “miracle tree” for offering a wide variety of ecosystem services and possessing strong ecological attributes. The multiple uses of leucaena in agroforestry, livestock, and restoration practices led to the worldwide distribution of its ssp. glabrata and leucocephala. However, following its introduction into non-native regions, the commercial value of ssp. leucocephala was challenged by its large-scale spread outside the cultivation zone. It has assumed a status of an environmental weed and invasive plant in many regions across Africa (17 countries and Island nations), Asia (17), Europe (1), Oceania (23), North America (12), and South America (7). The plant is enlisted in the top five terrestrial invasive plant species with the greatest international presence. The species is now considered one of the 100 worst invaders in the world. The plant mainly invades roadsides, wastelands, cultivated lands, riverbanks, and forest edges, and suppresses the growth of other woody and herbaceous species. Its infestations alter the patterns of vegetation, plant succession, and community assembly in the introduced habitats. Propagation of ssp. leucocephala, without considering the environmental risks associated with it, may result in major repercussions and irreparable losses. Therefore, it is important to discuss its invasive propensities and the possible alternatives that may replace the weedy species without encumbering its economic benefits. This review aims to thoroughly evaluate the ecological and invasive attributes of leucaena, promote awareness about the ecological costs associated with its spread, and suggest suitable options for its management.